Ramadan on Campus - Noraisah Nurul Fatwa, Mohd Razali (UMPSA, 2024)
In the campus's hallowed halls, Ramadan's grace, Students, away from home, find a sacred space, Fasting from dawn till dusk, a spiritual quest, In unity, they break with zest